USE OF THE LABORATORY OF MANAGEMENT IN THE PROCESS OF LEARNING FROM THE PERSPECTIVE OF THE REVISED BLOOM'S TAXONOMY - Souza, Crisomar Lobo de; Sauaia, Antonio Carlos Aidar; Oliva, Fábio Lotti (Pensamento & Realidade, 2019)
This study illustrates how the activities of the laboratory of management can contribute to generate interest and improve the process of student learning. The article analyzes the activities generated in the laboratory of management with the revised Bloom's taxonomy. Potential effects and benefits of the teaching and learning of these activities associated with the revised Bloom's taxonomy will be discussed. Therefore, the objective of this study is to report the whole process of learning during the classes of laboratory management (SIMULAB). The primary data were collected from companies that participated in the laboratory of management through the completion of forms of decision-making and results obtained in the SIMULAB. In addition to the collection of data, was conducted interviews with students of participating companies. The study showed that during the development of activities in the SIMULAB led the students to create innovative projects to compete among themselves as a result. Furthermore, it was observed that the students participated actively in the process of development of activities.